Efektivitas Pemanfaatan Cyberspace dalam Penguatan Moderasi Beragama di Kalangan Mahasiswa Perguruan Tinggi Keagamaan Islam Swasta - Astuti, Efi Tri (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – Religious moderation in the digital era, especially in higher education, is critical to counter the spread of radicalism online and foster a tolerant, inclusive youth. This study aims to: (1) examine the use of cyberspace in promoting students’ religious moderation at Muhammadiyah Pacitan Islamic Study Institute, and (2) evaluate the effectiveness of cyberspace in achieving this goal.Method – A quantitative approach with an experimental method was employed, involving an experimental and a control group. Forty students were selected through proportionate stratified random sampling. Data collection utilized tests, observations, and interviews, with analysis conducted using N-Gain Scores and Independent Sample T-Tests.Findings – The study revealed that cyberspace is moderately effective in teaching religious moderation, with an average N-Gain Score of 57% in the experimental group, categorized as